PENGARUH KEGIATAN MENGGAMBAR DENGAN LIDI DAN TINTA TERHADAP KEMAMPUAN KOORDINASI MATA DAN TANGAN ANAK KELOMPOK B DI RA ASYIFA 3 BANUAYU - Yuniar, Intan; Septiani, Yin Yin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of drawing with stick and ink on the hand-eye coordination skills of children in Group B at RA Asyifa 3 Banuayu. The method used was quantitative with a one-shot case study design, and the sampling technique used was purposive sampling, with 15 children. Data collection used a performance test sheet to measure children's hand-eye coordination skills after treatment. Data analysis was performed using SPSS through normality tests and t-tests. The results showed that thcalculated t value was 2.10 and the table t value was 1.761, so the calculated t value ≥ tvalue (2.10 ≥ 1.761), meaning Ha was accepted and Ho was rejected. Thus, there was a significant effect of drawing with stick and ink on the hand-eye coordination skills of children in Group B at RA Asyifa 3 Banuayu. In conclusion, drawing with stick and ink significantly impacts children's hand-eye coordination skills.